Effectiveness of «Soilbiotics» application on winter wheat - Маренич, М. М.; Маркіна, І. А.; Гангур, В. В.; Лень, О. І. (Scientific Progress & Innovations, 2018)
In the presented studies, pre-planting seed treatment increased the yield of grain by 0.43 t/ha, which is almost 12 %. Taking into account the high grazing rate for seed of cereal crops with a continuous sowing method, the cost of using the full recommended standard for the seed treatment would be about 25 % of the total production costs of the cultivation technology. So it is a significant additional production costs, which, in the current financial situation, the vast majority of agribusinesses are not able to invest in crop growing technology. In this regard, we have chosen the minimum rate of application of the drug 1.0 l/ton of seeds. Although calculations show that even the maximum rate of use of «1R Seed Treatment» for reaching an increase in winter wheat yield of 0.5 t/ha will be economically feasible. In the variants of the experiment, in which the seeds of the pre-planting treatment were used for root crop fertilization with «4R Foliar Concentrate», the yield increase of winter wheat grain was 0.76 t/ha or almost 21 % compared with the control. Application of 2 kg/ha «4R Foliar Concentrate» to the phase of the tube led to a further increase in yield, which was 23.1 %. The most effective in the described experiment was the variant, where the pre-sowing treatment of seeds with humate was combined with fecal application, but the leaf application was carried out in two receptions of 1 kg/ha «4R Foliar Concentrate». The yield increase was 27 %, which confirms the recommendations of the manufacturer of these drugs and the leading European companies regarding the use of their own products for a multiple entry. In the experiment block, which used only leaf application, the effectiveness of the drug «4R Foliar Concentrate» was significant. Only one treatment of the crop with the drug in the phase of release into the tube contributed to an increase in yield of 0.27 t/ha or 7.4 %. An increase in the rate of use of the drug up to 2 kg/ha has a stronger effect and increased the yield of winter wheat grain, compared with the control, by 0.38 t/ha or 10.5 %. A fractional introduction of the same norm into different phases of the development of culture is accompanied by an increase in yields by 0.50 t/ha, compared with the option without fertilization and increases additional profits, compared with the single use of the entire drug norm. Thus, differentiated use of drugs was more effective than single use. Studies have shown the effectiveness of the use of humates in winter wheat cultivation technology, in particular, «1R Seed Treatment» and growth stimulator «4R Foliar Concentrate». The combination of pre-sowing seed treatment and leaf application of crops enables to increase the yield of winter wheat by 11.8–27 %, and the use of sheet-laying applications only provides grain growth within the range of 7.4–13.8 %. The differentiated application of growth promoter «4R Foliar Concentrate» has a better economic and economic effect than a one-time use.